Multiple lentigines syndrome - LEOPARD syndrome. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
Multiple lentigines syndrome - LEOPARD syndrome (Lentigines, Electrocardiographic abnormalities, Ocular hypertelorism, Pulmonary stenosis, Abnormalities of the genitalia, Retardation of growth and Deafness).